Transatlantic Upper Canada : portraits in literature, land, and British-Indigenous relations - Hutchings, Kevin (Kevin Douglas), 1960- (McGill-Queen's transatlantic studies ;, 2020)
"Literature emerging from nineteenth-century Upper Canada, born of dramatic cultural and political collisions, reveals much about the colony's history through its contrasting understandings of nature, ecology, deforestation, agricultural development, and land rights. In the first detailed study of literary interactions between Indigenous people and colonial authorities in Upper Canada and Britain, Kevin Hutchings analyzes the period's key figures and the central role that romanticism, ecology, and environment played in their writings. Investigating the ties that bound Upper Canada and Great Britain together during the early nineteenth century, Transatlantic Upper Canada demonstrates the existence of a cosmopolitan culture whose implications for the land and its people are still felt today. The book examines the writings of Haudenosaunee leaders John Norton and John Brant and Anishinabeg authors Jane Johnston Schoolcraft, Peter Jones, and George Copway, as well as European figures John Beverley Robinson, John Strachan, Anna Brownell Jameson, and Sir Francis Bond Head. Hutchings argues that, despite their cultural differences, many factors connected these writers, including shared literary interests, cross-Atlantic journeys, metropolitan experiences, mutual acquaintance, and engagement in ongoing dialogue over Indigenous territory and governance. A close examination of relationships between peoples and their understandings of land, Transatlantic Upper Canada creates a rich portrait of the nineteenth-century British Atlantic world and the cultural and environmental consequences of colonialism and resistance. "--